Anti-N-methyl-D-aspartate receptor encephalitis mimics neuroleptic malignant syndrome: case report and literature review - Wang HY (Dove Medical Press, 2019)
Hai-Yang Wang,1 Tian Li,2,3 Xue-Lin Li,4 Xiao-Xia Zhang,1 Zhong-Rui Yan,1 Yang Xu1 1Department of Neurology, Jining No 1 People’s Hospital, Jining, Shandong Province, People’s Republic of China; 2Department of Cardiology, Jining No 1 People’s Hospital, Jining, Shandong Province, People’s Republic of China; 3Department of Internal Medicine-Cardiovascular, Qilu Hospital of Shandong University, Jinan, Shandong Province, People’s Republic of China; 4Department of Intensive Care Unit, Jining No 1 People’s Hospital, Jining, Shandong Province, People’s Republic of China Background: Anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis is a severe autoimmune disease characterized by complicated psychiatric and neurological symptoms and a difficult diagnosis. This disorder is commonly misdiagnosed, and diagnosis is often delayed. The clinical signs can mimic other psychiatric abnormalities, such as neuroleptic malignant syndrome (NMS) that is usually caused by antipsychotic exposure. This fact raises the question of whether the symptoms common to NMS are due to anti-NMDA receptor encephalitis or established NMS.Cases presentation: We describe a rare case of a 29-year-old male without psychiatric history who initially presented with a fever, altered consciousness, behavioral changes, rigidity, and elevated creatine kinase. He was initially diagnosed with NMS. NMS-like symptoms did not improve with active treatments and disappeared for a long period after discontinuing antipsychotics. The patient gradually developed a complicated disease progression, including speech impairment, mutism, and movement disorders, and symptom progression led to the final diagnosis of anti-NMDA receptor encephalitis. The related pathophysiological mechanisms, clinical features, and treatment of this disease are reviewed.Conclusion: We highlight that the natural progress of anti-NMDA receptor encephalitis can mimic the symptoms of NMS and NMS-like features could be due to anti-NMDA receptor encephalitis upon antipsychotic exposure, and not true NMS. Clinically, the suspicion of NMS may serve as a significant alarm to suspect anti-NMDA receptor encephalitis and lead neurologists or psychiatrists to investigate such a diagnosis. Keywords: acute psychosis, anti-NMDA receptor encephalitis, autoimmune encephalitis, neuroleptic malignant syndrome, antipsychotics, diagnosis